2020
DOI: 10.5098/hmt.14.18
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Blasius and Sakiadis Flows With Variable Thermal Conductivity in the Presence of Thermal Radiation and Viscous Dissipation

Abstract: A theoretical analysis has been carried out to investigate the influence of unsteadiness on the laminar two-phase magnetohydrodynamic nanofluid flow filled with porous medium under the combined effects of Brownian motion and thermophoresis. Thermal variable conductivity, thermal radiation and viscous dissipation effects are also considered in this numerical study. The highly nonlinear partial differential equations are transformed into a set of coupled nonlinear ordinary differential equations through suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The coupled system of Equations (20) and (21) , along with the boundary conditions specified in Equation (22) , is solved using the SQLM [48] , [49] , [50] , [51] , [52] . These equations are expressed using nonlinear ordinary differential systems.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled system of Equations (20) and (21) , along with the boundary conditions specified in Equation (22) , is solved using the SQLM [48] , [49] , [50] , [51] , [52] . These equations are expressed using nonlinear ordinary differential systems.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
“…Occasionally, this approach exhibited slow convergence or even failed to yield a solution. However, it was reported that the utilization of SQLM demonstrates a significantly higher convergence rate compared to existing numerical techniques, and its iterative steps are relatively straightforward to implement [50] , [51] , [52] . The distinctive feature of SQLM, contributing to its widespread acceptance as a numerical technique, was reported to be its ability to break down a complex set of nonlinear equations into smaller subsystems that are inherently more manageable.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
“…The influence of magnetized variable thermal conductivity on the flow and heat transfer characteristics of an unstable Williamson fluid was studied by Shankar et al (2020). Shateyi and Muzara (2020) studied the unsteady MHD Blasius and Sakiadis flows with variable thermal conductivity in the presence of thermal radiation and viscous dissipation. The research of the MHD flow of Casson nanofluid across an infinite exponential porous surface in a rotating frame in the presence of slip velocity was explored by VeerKrishna et al (2021).…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…By wrapping a stretched surface around a binary chemical process, a Casson fluid can be activated by an electrically conducting, incompressible fluid (Vijaya et al [38]). In order to investigate the instability of laminar two-phase MHD nanofluid flow with porous media under Brownian motion, thermophoresis, and changing thermal conductivity, Stanford Shateyi and Hillary Muzara [39] used Brownian motion, thermophoresis, and changing thermal conductivity. Free convection was investigated by Askasasbeh et al [40] over a sheet subjected to constant wall temperatures.…”
Section: Introductionmentioning
confidence: 99%